The Difference In Blood Pressure Increase In Coffee Drinkers Versus Smokers In Medan City - Arifin, Muhammad Osama; Harahap, Rini Syahrani (Buletin Farmatera, 2026)
Abstract: Coffee affects Blood pressure via polyphenols, potassium, and caffeine. Polyphenols and potassium work to lower blood pressure. Nicotine causes addiction by stimulating dopamine growth in the brain and activating the rewards pathway. Research Method: Quantitative descriptive research with a cross-sectional study approach aimed at the community of Jalan Halat, Medan City, with the measurement of respondents' blood pressure 1-2 hours after drinking coffee or smoking. Results: The results of the study showed an increase in blood pressure, both systolic and diastolic, in the smoking and coffee drinking groups. Through the Mann-Whitney test,  p-value for systolic blood pressure of 0.000 0.05 was obtained, which means there is a significant difference in the increase in systolic blood pressure between the smoking and coffee drinking groups. Meanwhile, for diastolic blood pressure,  p-value of 0.000 0.05 was obtained, which means there is a significant difference in the increase in diastolic blood pressure between the smoking and coffee drinking groups. Conclusion: There is a significant difference in the increase of both systolic and diastolic blood pressure in the smoking and coffee drinking groups on Jalan Halat, Medan City.